BETWEEN CULTURE AND REGULATIONS FOR WOMEN WORKERS IN THE TOURISM FUTURE - Ketut Sari Adnyani; Ni Putu Ega Parwati; Komang Febrinayanti Dantes (Universitas Tabanan, 2025)
In accordance with Decree MUDP X/2010 which legitimizes women to be involved and play an active role like men in the public and domestic spheres. Socio-legal research, data in the form of legal documents and the results of in-depth interviews are then analyzed using various approaches (legal, theoretical and historical approaches) using inductive-deductive methods. The research results show that Bali Provincial Regulation 5 of 2020 accommodates the role of indigenous communities, including indigenous women, in managing Balinese cultural tourism, therefore Law Number 10 of 2009 is the only reference in managing Balinese cultural tourism. Meanwhile, for Balinese traditional communities, it is known that participation is not only regulated in Bali Provincial Regulation Number 4 of 2019 concerning traditional villages and awig-awig, but also in unwritten forms such as pararem pemahcah awig and perarem, ngele. The existence of indigenous women as public sector workers, namely in tourist villages, is not only found in actual texts, but in general they live their lives based on customary law which contains applicable values, principles and norms. Therefore, it is necessary to formulate tourism policies that accommodate the rights of women indigenous workers in the substance of more specific customary law as a source of gender responsiveness.